Laporan Pertama Kasus Infestasi Spinturnix spp. pada Kelelawar Pemakan Buah (Rousettus spp.) - Audina Putri Geraldine; Citra Kurnia Putri; Ryanka Edila; Aditya Yudhana; Fransiska Okta Zania (Universitas Airlangga, 2022)
Rousettus spp. is one of the wild animals that may transmit various diseases including zoonotic. Rousettus spp. or known as fruit bat is found in Java island and belongs to the Pteropodidae family. Generally, Rousettus spp. consumes fruit and floral products. This case report aims to detect ectoparasites in fruit bats (Rousettus spp.) found at Djawatan Banyuwangi, East Java. The samples in this case report are seven fruit bats (Rousettus spp.). Based on the results of laboratory identification using the whole mount method, from 7 samples of fruit bats (Rousettus spp.), there are five fruit bats (Rousettus spp.) were infected with Spinturnix spp.. Spinturnix spp. that obtained from fruit bats (Rousettus spp.) were examined using a binocular microscope (Olympus CX-23, Tokyo Japan) with a magnification of 100 times. Images of ectoparasites and bats were taken using a Nikon d5300 camera. Total amount of Spinturnix spp. that was successfully obtained from 5 fruit bats (Rousettus spp.) are 25 individuals.